Cyclicyte De La Politique Monetaire Et Croissance Economique En Afrique Sub-Saharienne : Le Role De La Gouvernance Des Institutions (Global Journal of Management and Business Research, 2020)
The objective of this paper is to assess the effect of institutional governance on the relationship between the reaction of monetary authorities when the economy faces a shock and economic growth in the countries of the Sub-Saharan Africa. To achieve this, econometric estimates were made using the Generalized Moment Method (MMG) in a dynamic panel of 36 countries in the zone over the period from 2000 to 2018. The results obtained show that monetary policy as a policy macroeconomic is not a tool for stabilizing economic activity. This low level of democracy in these countries therefore has the effect of amplifying this pro-cyclical behavior of monetary policy. Governments genuinely infer in the implementation of monetary policies, thereby causing this pro-cyclical bias. The independence of the central bank and membership of a flexible exchange rate regime considerably reduce the pro-cyclicality of monetary policy in the countries of sub-Saharan Africa. The quality of the governance of institutions has optimal potential for promoting economic growth in Sub-Saharan Africa.
Keywords: institutional governance; cyclical monetary policy; economic growth; MMG